TELEVİZYON İZLEME SÜRESİNİN OKUL ÖNCESİ EĞİTİM KURUMUNA DEVAM EDEN 60-72 AYLIK ÇOCUKLARIN SOSYAL BECERİLERİ ÜZERİNDEKİ ETKİSİNİN İNCELENMESİ - (:unkn) unknown (My University, 2015)
Günümüzde son derece yaygın bir kitle iletişim aracı olan televizyonun bireyler üzerindeki etkileri son yıllarda üzerinde sıkça tartışılan bir konu haline gelmiştir. Özellikle görsel ve işitsel uyaranların bir arada olması televizyonun diğer kitle iletişim araçları arasında etki gücünü artırmaktadır. Bu araştırmada, televizyon (TV) izleme süresinin 60-72 aylık çocukların sosyal becerileri üzerindeki etkisinin incelenmesi amaçlanmıştır. Araştırma tarama modelinde yürütülmüştür. Araştırmanın evrenini Samsun ili merkez ilçelerinde okul öncesi eğitime devam eden 60-72 aylık çocuklar oluşturmuştur. Araştırmanın örneklemini ise Samsun ilinde Atakum, İlkadım, Canik ve Tekkeköy merkez ilçelerinde yer alan, Milli Eğitim Bakanlığı'na bağlı özel ve bağımsız anaokullarına devam eden 60-72 aylık 498 çocuk oluşturmuştur. Araştırmada verilerin toplanmasında bir anket formu ile "Anaokulu ve Anasınıfı Davranış Ölçeği" kullanılmıştır. Yapılan analizlerde betimsel istatistik (frekans, yüzdeler, ortalamalar ve standart sapmalar), iki faktörlü ANOVA, Post-Hoc çoklu karşılaştırma testlerinden Tamhane's T2 ve Scheffe testleri kullanılmıştır. Elde edilen bulgular doğrultusunda çocukların sosyal becerileri TV izleme sürelerine göre incelendiğinde daha uzun süre TV izleyen çocukların sosyal becerileri kısa süre izleyenlere göre daha yüksek düzeyde bulunmuştur. Ayrıca TV izleme süresi ve anne öğrenim durumu birlikte incelendiğinde çocukların sosyal becerileri üzerinde etkili olduğu bulunmuştur. Ayrıca çocukların sosyal becerilerinin cinsiyete, baba öğrenim düzeyine, kardeş sayısına ve anne çalışma durumuna göre farklılaşmadığı saptanmıştır. Araştırmanın sonuçları ilgili literatür kapsamında bulunulmuştur. tartışılmış, araştırmacılara yönelik önerilerde

Television, as an important mass media, enters almost every home and becomes a part of our lives. As an inseparable part of our lives, television has a great potential to influence the feelings, thoughts, beliefs, attitudes and behaviors of individuals. Therefore, the impact of television (both the duration of television viewing and the content of programs) on children and adults has been increasingly investigated in the recent years. Studies in the related literature mainly focus on issues such as the impact of television on children, duration of television viewing in children, the content of the programs, television viewing frequency and why we watch television (Akar, 2002; Basal, 2002; Bırgul, 1999; Buyukbaykal, 2007; Frey ve Benesch, 2008; Keating, 2011; Martin, Coulon, Markward, Greenway ve Anton, 2009; Okur, 2000; Ozkan, 2006). It is known that the duration of television viewing may vary by different factors such as children’s age, education level of parents, mother's working status, the presence of elder or younger siblings, airing hours and family control over children's television viewing behavior (Mangır and Inal, 1994). Özdiker (2002) investigated the duration of television viewing in children and reported the following results; 30.79% of children watch television for 2-3 hours, 25.63% for 2 hours, 17.94% for 3-4 hours a day and 25.64% limitlessly. It was reported in a study conducted by Yalcin Tugrul, Nacer, Tuncer and Yurdakök (2002) that 62% of children watch television for more than two hours and 8.3% watch television for more than 4 hours a day. These studies have shed light to new studies investigating the influence of television viewing duration on children. In this study, the effects of television viewing duration on social skill levels of children (aged 60-72 months) attending pre-school education institutions were examined with respect to various variables. Thus, the aim of this study is to examine the effects of television viewing duration on social skill levels of preschool children aged 60-72 months. In this context, we seek an answer to the following questions; 1. Do children's social skills differ significantly in terms of gender and the duration of television viewing? 2. Do children's social skills differ significantly in terms of the duration of television viewing and mother's educational status? 3. Do children's social skills differ significantly in terms of the duration of television viewing and father's educational status? 4. Do children's social skills differ significantly in terms of the duration of television viewing and the number of siblings? 5. Do children's social skills differ significantly in terms of the duration of television viewing and mother's working status?
A STUDY ON ANALYZING THE EFFECT OF DURATION OF TELEVISION WATCHING ON SOCIAL SKILLS OF 60-72 MONTH-OLD CHILDREN